Optimization And Characterization of Silver Nanoparticle Biosynthesis Using Parijoto Fruit (Medinilla speciosa) Water Extract With Box-Behnken Design - Nurjana, Qinta Laily; Amin, Azizah; Annisa, Viviane; Munawiroh, Siti Zahliyatul (Integrated Research and Testing Laboratory (LPPT) Universitas Gadjah Mada, 2025)
Silver nanoparticles in the medical field are used as additives in vaccines, anti-diabetic agents, wound and bone healing, biosensors and anticancer therapy in medical applications. One of the plants that can act as a reducing agent in the biosynthesis of silver nanoparticles is the parijoto fruit (Medinilla speciosa). This study aims to optimize and characterize the biosynthesis of silver nanoparticles from the water extract of parijoto fruit (M. speciosa) with a box-behnken design. The method used in this study starts from the manufacture of water extract of parijoto fruit (M. speciosa) then continued with the biosynthesis of silver nanoparticles. The formula for the biosynthesis of silver nanoparticles will be optimized with a box-behnken design and characterized by Particle Size Analyzer (PSA), Fourier Transform Infrared (FTIR), and Transmission Electron Microscopy (TEM). The results obtained in this study will be analyzed using descriptive techniques. The optimization results with the Behnken box design showed an optimal formula with an extract concentration of 1%, a sonication time of 6 minutes, and a sonicator pulser of 30. The particle size obtained was 85 ± 0.1 nm with a PI of 0.486 ± 0.006 and a zeta potential of -27.3 ± 1.5. The FTIR spectrum showed C=O, C-O and O-H groups indicating flavonoid compounds as bioreductant agents. The morphology of silver nanoparticles showed instability. (4) Conclusions:the optimization of silver nanoparticles from parijoto fruit water extract (M. speciosa) have been discovered used the Box-Behnken design and has good silver nanoparticle characteristics.